Menakar Ulang Otoritas Keluarga Dalam Penyelesaian Sengketa Pada Sistem Kekerabatan Matrilineal, Patrilineal, Dan Bilateral - Rika Syafitri; Zulfan; Elfia (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2026)
Family dispute resolution within Indonesia's pluralistic society frequently transcends formal legal mechanisms, relying instead on kinship structures endowed with profound social legitimacy. This article aims to critically examine how diverse kinship systems matrilineal, patrilineal, and parental/bilateral shape the distribution and operation of family authority in conflict resolution. Employing a literature-based research method with conceptual and comparative approaches, the data is analyzed qualitatively. The findings demonstrate that family authority is not a universal given, but rather a social construct dictated by the adopted kinship architecture. In matrilineal societies, authority is exercised through communitarian solidarity represented by the mamak; in patrilineal societies, it is entrenched in a genealogical hierarchy positioning senior male relatives as the central patrons; whereas in bilateral societies, authority is formulated through egalitarian deliberation and consensus involving both maternal and paternal lines. Ultimately, this study posits that family authority serves as the crucial intersection between kinship structures and dispute resolution mechanisms. The effectiveness of conflict resolution is thus determined not merely by formal procedural norms, but by the degree of social legitimacy and acceptance the authority figures command from the disputing parties. Consequently, the family endures as a vital socio-legal institution in preserving social equilibrium and orchestrating dispute resolution within Indonesia's legally pluralistic landscape.